Die Abraham-motief in Matteus 1-4 - Nortj, L. (Verbum et ecclesia, 1998)
The Abraham-motive in Matthew 1-4 Matthew’s indication of Jesus as the Son of David and the Son of Abraham develop along two lines in Matthew’s story. Firstly, is Jesus portrayed as the Son of David, who represents the "Jewish" line in the story. And secondly Matthew is using Jesus as Son of Abraham to develop the "gentile" line in the story. Matthew uses the Abraham motives in chapters 1-4 to illustrate the inclusion of the gentiles into the new people of God. Under discussion are the gentile women in the genealogy and other possible motives that reflect the story of Abraham.